Pengaruh Kinerja Lingkungan dan Corporate Social Responsibility (CSR) Terhadap Kinerja Keuangan Perusahaan Yang Terdaftar di Jakarta Islamic Index (JII) Periode 2022-2024 - Nia Ramadani; Usdeldi .; Fitri Ana Siregar (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study examines the effect of Environmental Performance and Corporate social responsibility (CSR) on the financial performance of companies listed in the Jakarta islamic index (JII) during the 2022–2024 period. Financial performance is measured using Return on Assets (ROA). This study employs a quantitative approach using secondary data obtained from annual and sustainability reports of companies listed in JII. The data were analyzed using panel data regression analysis. The results show that Environmental Performance has no significant effect on ROA. In contrast, CSR has a negative and significant effect on ROA. Simultaneously, Environmental Performance and CSR significantly affect ROA, indicating that both variables jointly contribute to explaining changes in corporate financial performance. Companies should implement CSR programs more effectively and strategically to ensure that social responsibility activities contribute to long-term financial performance. Investors may also consider environmental and CSR disclosures as indicators of corporate sustainability when making investment decisions. This study extends previous research by focusing on companies listed in the Jakarta islamic index (JII) during the 2022–2024 period. It provides updated empirical evidence on the relationship between Environmental Performance, CSR, and financial performance within the context of the Indonesian Islamic capital market